Éthique et esthétique dans l’œuvre d’Alexandre Najjar - Meriem Boughachiche (Multilinguales)
The work of Alexandre Najjar is fully in line with a filiation, a movement and a literary lineage in which the question of ethics and aesthetics is fundamental while at the same time standing out. Nourished by the sap of a universal humanism, the French-speaking Lebanese writer and lawyer invites us to explore his world and his imagination through the art of discourse. This gift that is cultivated, the lawyer transposes it into the romantic universe where the speaker meets the writer, a beautiful encounter with rational and passionate speech. And beyond the moral and aesthetic ideal, writing builds a temple of effective eloquence and eternal utopia : an overflowing humanism. The aim is therefore to question the relationship between law and literature in the work of Alexandre Najjar through the problematic of ethics and aesthetics. If the law/literature relationship moves in a pertinently dialectical field of reflection, it is also the meeting place of two fruitful imaginations for human thought. Such seems to be the vision in which the work of Alexandre Najjar is rooted, which cannot be conceived apart from a principle and an ambition : to render justice, on the model of writing, in a fragmented and plural, freedom and cultural resistance.